Hypocomplementemia in systemic sclerosis - G. Valentini; S. Vettori; L. Ruocco; G. Abignano; G. Cuomo (PAGEPress Publications, 2011)
Background: Hypocomplementemia has been detected in about 15% of unselected series of SSc patients. It constitutes one of the 10 parameters needed to evaluate the European Scleroderma Study Group (EScSG) activity index. A few studies have been so far devoted to investigate the clinical manifestations correlated with this finding. Objective: To investigate SSc patients for hypocomplementemia and point out clinical manifestations associated with it. Methods: 302 patients with SSc consecutively admitted to the Rheumatology Unit of the Second University of Naples were enrolled in the study. SSc patients were all investigated for sex, age, disease duration, clinical and serological subset, disease activity, organ/system severity and functional status. Patients were divided into 2 groups: normo-complementemic and hypocomplementemic (low C3 and/or C4) as measured by nephelometry. Results: 252 of the 302 patients had normal complementemia; 50 (16,5%) had hypocomplementemia. Significant associations were found between hypocomplementemia and EScSG activity index (p<0.0003); functional disability (i.e. HAQ-DI >0.5)( p=0.04); and the severity of general manifestations (p<0.006); skin (p<0.0001); vascular (p<0.0001); heart (p<0.0001) and lung (p<0.0001) involvement. Conclusions: Our study confirms that hypocomplementemia occurs in patients with SSc. It resulted to be associated with disease activity, functional status and the severity of distinct disease manifestations